PROSES BERPIKIR SISWA SEKOLAH DASAR DALAM PEMECAHAN MASALAH MATEMATIS PADA MATERI OPERASI HITUNG CAMPURAN - Wahid Umar; Pamuti Pamuti (Universitas Khairun, 2021)
This research includes qualitative research. Qualitative research is research that examines phenomena in a state of potency and attempts to describe these phenomena. The phenomenon studied in this study is the way of solving and thinking processes of students in mathematical problem solving related to mixed arithmetic operations by fourth grade elementary school students. The method of solving the problem will be studied according to the four steps of Polya's problem solving, namely: (a) understanding the problem; (b) planning solutions; (c) solving problems; (d) re-examine the results of the work. In this paper, we will discuss how to solve a student's problem and his thinking process in solving mathematical problems related to mixed arithmetic operations.